Urinary Tract Infections in Adults - Evan B. Cohn; Anthony J. Schaeffer (The Scientific World Journal)
Urinary tract infection (UTI) is an exceedingly common problem prompting seven million office visits and one million hospitalizations in the United States each year (1). Advances in the understanding of both host and bacterial factors involved in UTI have led to many improvements in therapy. While there have also been advances in the realm of antimicrobials, there have been numerous problems with multiple drug resistant organisms. Providing economical care while minimizing drug resistance requires appropriate diagnosis, evaluation, and treatment of urinary tract infections.